Trends in U.S. Mass Shootings: Facts, Fears and Fatalities - Fox, James Alan (Journal of contemporary criminal justice, 2024)
Although representing a rather small percentage of gun deaths in the United States, mass shootings receive a disproportionate share of crime news coverage, with the fears of countless Americans at a level well above the actual risk. This article attempts to clarify some of the wide-ranging confusion regarding what exactly is a mass shooting, how often they occur, and whether they have been on the rise over the past several years. After discussion of some methodological issues associated with measuring prevalence, trends exhibited in several reliable data sources on mass shooting are presented. The article concludes with a brief discussion of contagion and whether it is reasonable to expect that the recent spike in mass shootings will persist.